School-based health education effect on knowledge, attitude, and practices of dengue prevention among school children: a systematic review - Dapari, Rahmat; Jumidey, Abdul Qayyum; Abdul Manaf, Rosliza; Ahmad Zamzuri, Mohd ‘Ammar Ihsan; Hassan, Mohd Rohaizat; Dom, Nazri Che; Syed Abdul Rahim, Syed Sharizman (Springer Nature, 2025)
Introduction: Dengue is a mosquito-borne viral disease caused by dengue virus. The incidence of dengue has been steadily increasing globally in recent decades. The main treatment modality focuses on symptomatic relief. Primary prevention such as vector control and community education remain the mainstay of dengue control. School-based health education is one of the commonly applied interventions among school-age children to improve dengue control. Objective: This systematic review aimed to systematically analyse and determine the impact of various school-based health education programmes on the knowledge, attitudes, and practices of dengue prevention among school children. Methods: Articles related to school-based health education with dengue prevention were retrieved electronically from three different databases (EBSCOhost-Medline, Scopus, and Pubmed). Articles were screened by independent reviewers. Selected articles based on the inclusion and exclusion criteria were stored in Microsoft Excel. All included articles were critically appraised to assess the quality of the studies using the Mixed Method Appraisal Tool (MMAT). Results: Of the 582 articles identified, nine were included in the final review. Overall, there was an increase in knowledge, attitude, and practice regarding dengue following school-based health education. However, knowledge appeared to be the most significant variable as all studies showed a significant increase in knowledge. Hence, educational interventions exerted a more prominent impact on the knowledge of dengue infection compared to attitude and practices among school children. Conclusion: Further research is warranted to establish stronger evidence and evaluate the long-term impact of these interventions on students’ knowledge, attitudes, and practice.